Cumulative Incidence of Cancer Among Persons With HIV in North America: A Cohort Study. - Silverberg, Michael J; Lau, Bryan; Achenbach, Chad J; Jing, Yuezhou; Althoff, Keri N; D'Souza, Gypsyamber; Engels, Eric A; Hessol, Nancy A; Brooks, John T; Burchell, Ann N; Gill, M John; Goedert, James J; et al. (Annals of internal medicine, 2015)
Cancer is increasingly common among persons with HIV.